2020
DOI: 10.1101/2020.09.11.291724
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Cardiac Cell Type-Specific Gene Regulatory Programs and Disease Risk Association

Abstract: BackgroundCis-regulatory elements such as enhancers and promoters are crucial for directing gene expression in the human heart. Dysregulation of these elements can result in many cardiovascular diseases that are major leading causes of morbidity and mortality worldwide. In addition, genetic variants associated with cardiovascular disease risk are enriched within cis-regulatory elements. However, the location and activity of these cis-regulatory elements in individual cardiac cell types remains to be fully defi… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(22 citation statements)
references
References 137 publications
(176 reference statements)
1
21
0
Order By: Relevance
“…Together, these findings are in line with recent characterizations of unexpected cardiogenic gene programs in cardiac fibroblasts (Furtado et al, 2014). We finally compared subtype-specific cCREs with chromatin profiles from in vitro cultured fibroblast biosamples and cardiac fibroblasts from sci-ATAC-seq (Hocker et al, 2020). While all fibroblast subtypes from the current study showed similarity to in vitro fibroblasts based on core fibroblast cCRE signatures, only the fibroblast subtype Fib.3 matched previously reported cardiac fibroblasts based on subtype-specific fibroblast cCRE signatures ( Figure 5F), suggesting that fibroblast subtypespecific signatures are environment dependent and may be lost during in vitro culturing.…”
supporting
confidence: 78%
See 4 more Smart Citations
“…Together, these findings are in line with recent characterizations of unexpected cardiogenic gene programs in cardiac fibroblasts (Furtado et al, 2014). We finally compared subtype-specific cCREs with chromatin profiles from in vitro cultured fibroblast biosamples and cardiac fibroblasts from sci-ATAC-seq (Hocker et al, 2020). While all fibroblast subtypes from the current study showed similarity to in vitro fibroblasts based on core fibroblast cCRE signatures, only the fibroblast subtype Fib.3 matched previously reported cardiac fibroblasts based on subtype-specific fibroblast cCRE signatures ( Figure 5F), suggesting that fibroblast subtypespecific signatures are environment dependent and may be lost during in vitro culturing.…”
supporting
confidence: 78%
“…We thus optimized nuclear isolation methods and buffer conditions for each tissue type (Table S2, see Methods). Subsequently, we generated sci-ATACseq datasets using a semi-automated workflow (Hocker et al, 2020;Li et al, 2020;Preissl et al, 2018) and sequenced resulting libraries to 7,651 raw sequence reads per nucleus on average, with a median read duplication rate of 44% (Table S3). Open chromatin fragments from these libraries were computationally assigned to individual nuclei using nucleus-specific DNA barcodes.…”
Section: Single Cell Chromatin Accessibility Analysis Of Adult Human mentioning
confidence: 99%
See 3 more Smart Citations